2008
DOI: 10.1039/b805991h
|View full text |Cite
|
Sign up to set email alerts
|

Ambient site, home outdoor and home indoor particulate concentrations as proxies of personal exposures

Abstract: Despite strong longitudinal associations between particle personal exposures and ambient concentrations, previous studies have found considerable inter-personal variability in these associations. Factors contributing to this inter-personal variability are important to identify in order to improve our ability to assess particulate exposures for individuals. This paper examines whether ambient, home outdoor and home indoor particle concentrations can be used as proxies of corresponding personal exposures. We exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 35 publications
8
37
1
Order By: Relevance
“…This finding is unusual; of eleven recent studies, most showed mean personal exposures that were higher than mean outdoor concentrations (personal/outdoor ratios ranging from 0.8 to 2.5, compared to our ratio of 0.6, the lowest of all the studies) (Jannsen et al 1999;Pellizzari et al 1999;2001;Rojas-Bracho et al 2000;Williams et al 2000;Weisel et al 2005;Turpin et al 2007;Brown et al 2008). The DEARS study in the neighboring city of Detroit took place in the same years and resulted in similar mean outdoor PM 2.5 concentrations of about 16 µg/m 3 (Williams et al 2008), which is nearly identical to the mean of 15.9 µg/m 3 in Windsor; yet the mean indoor concentrations in Detroit were 19 µg/m 3 compared with 8 µg/m 3 in Windsor.…”
Section: Discussionmentioning
confidence: 44%
“…This finding is unusual; of eleven recent studies, most showed mean personal exposures that were higher than mean outdoor concentrations (personal/outdoor ratios ranging from 0.8 to 2.5, compared to our ratio of 0.6, the lowest of all the studies) (Jannsen et al 1999;Pellizzari et al 1999;2001;Rojas-Bracho et al 2000;Williams et al 2000;Weisel et al 2005;Turpin et al 2007;Brown et al 2008). The DEARS study in the neighboring city of Detroit took place in the same years and resulted in similar mean outdoor PM 2.5 concentrations of about 16 µg/m 3 (Williams et al 2008), which is nearly identical to the mean of 15.9 µg/m 3 in Windsor; yet the mean indoor concentrations in Detroit were 19 µg/m 3 compared with 8 µg/m 3 in Windsor.…”
Section: Discussionmentioning
confidence: 44%
“…Previous exposure studies focused on personal exposures and/or home indoor PM 2.5 mass concentrations, as most individuals spend a large fraction of time indoors at home. A number of these studies have also measured levels of PM 2.5 components, such as sulfate and EC (Sarnat et al, 2006;Brown et al, 2008). Furthermore, some exposure studies have shown that personal PM 2.5 mass exposures exceed corresponding outdoor or ambient particulate concentrations (Wallace et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The weak correlation (r s = 0.328, p = 0.055) between ambient and personal PM 2.5 and the intercept greater than zero from the regression analysis in Table 4 suggests that the non-ambient sources (e.g., indoor sources, personal activities) had a significant role in personal exposures. As reported in Brown et al (2008) and Rivas et al (2015), local traffic, indoor sources and/or personal activities can significantly affect the personal exposure to PM 2.5 and EC. Mohammadyan (2011) found that ambient PM and time spent in polluted microenvironments (e.g., buses) are the most important determinants of personal exposure to PM 2.5 .…”
Section: Relationship Between Personal Exposure and Ambient Concentramentioning
confidence: 99%